2021
DOI: 10.3389/fphar.2021.653035
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effect of Andrographolide Induced Autophagy on Random-Pattern Skin Flaps Survival

Abstract: Random-pattern skin flap replantation is generally used in the reconstruction of surgical tissues and covering a series of skin flap defects. However, ischemia often occurs at the flap distal parts, which lead to flap necrosis. Previous studies have shown that andrographolide (Andro) protects against ischemic cardiovascular diseases, but little is known about the effect of Andro on flap viability. Thus, our study aimed to building a model of random-pattern skin flap to understand the mechanism of Andro-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
(53 reference statements)
1
5
0
Order By: Relevance
“…This is similar to recent studies which found A. paniculata and its bioactive diterpenoids protected dermalfibroblasts and deratinocytes against inflammation and oxidative stress 194 . A recent study reported andrographolide increased random‐pattern skin flap survival by inducing autophagy 195 . These findings indicate that andrographolide may be available to treat skin diseases.…”
Section: Andrographolide In Inflammatory Diseasessupporting
confidence: 89%
See 1 more Smart Citation
“…This is similar to recent studies which found A. paniculata and its bioactive diterpenoids protected dermalfibroblasts and deratinocytes against inflammation and oxidative stress 194 . A recent study reported andrographolide increased random‐pattern skin flap survival by inducing autophagy 195 . These findings indicate that andrographolide may be available to treat skin diseases.…”
Section: Andrographolide In Inflammatory Diseasessupporting
confidence: 89%
“…194 A recent study reported andrographolide increased random-pattern skin flap survival by inducing autophagy. 195 These findings indicate that andrographolide may be available to treat skin diseases. For most skin diseases, topical administration of andrographolide may be more acceptable to patients.…”
Section: Inflammatory Skin Diseasesmentioning
confidence: 92%
“…Unfortunately, however, ischemia frequently occurs at the flap distal parts, which bring about flap necrosis. A recent work exhibited that, as a significant modulator of autophagy capable, andrographolide may prove fruitful for the increasing random‐pattern skin flap survival through enhancing angiogenesis, suppressing apoptosis and lessening oxidative stress (Jiang et al, 2021). Treatment of H9c2 cardiomyocytes and diabetic cardiomyopathy C57/BL6J mice with various concentrations of andrographolide resulted in a dose‐dependent inhibition of cardiac inflammation and oxidative stress, accompanied by reducing cardiac apoptosis, which the mechanism involve the modulation of NOX/Nrf2‐mediated oxidative stress and NF‐κ B‐mediated inflammation (Liang, Liu, Du, Yang, & Zhao, 2018).…”
Section: Pharmacologymentioning
confidence: 99%
“…Other compounds capable of stimulating autophagy have also been shown to be effective at promoting skin flap survival in various mouse and rat studies. These include catapol, a biologically active compound found in the flowering plant Rehmannia glutinosa , andorgrapholide, a diterpenoid isolated from the stem and leaves of Andrographis paniculata , and nobiletin, a flavonoid found in citrus fruits [ 56 , 58 57 ]. Each of these have been shown to positively regulate autophagy, through sirtuin 1, phophosoinositide 3-kinase/Akt, and 5′ adenosine monophosphate-activated protein kinase (AMPK) activation, respectively.…”
Section: Introductionmentioning
confidence: 99%